2006
DOI: 10.1158/1535-7163.mct-05-0302
|View full text |Cite
|
Sign up to set email alerts
|

Targeting signal transducer and activator of transcription 3 with G-quartet oligonucleotides: a potential novel therapy for head and neck cancer

Abstract: Signal transducer and activator of transcription 3 (Stat3) is a critical mediator of oncogenic signaling activated frequently in many types of human cancer where it contributes to tumor cell growth and resistance to apoptosis. Stat3 has been proposed as a promising target for anticancer drug discovery. Recently, we developed a series of G-quartet oligodeoxynucleotides (GQ-ODN) as novel and potent Stat3 inhibitors, which significantly suppressed the growth of prostate and breast tumors in nude mice. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 46 publications
(29 reference statements)
1
67
0
Order By: Relevance
“…G4DNA has been proposed as a drug target for treatment of cancer and other diseases (74). Our work here expands the rationale for targeting G4DNA and provides further support for G4DNA mimics as potential drugs (67,68).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…G4DNA has been proposed as a drug target for treatment of cancer and other diseases (74). Our work here expands the rationale for targeting G4DNA and provides further support for G4DNA mimics as potential drugs (67,68).…”
Section: Discussionsupporting
confidence: 63%
“…Several laboratories have reported that many cell types, usually cancer cells, spontaneously take up exogenous G4DNA (67)(68)(69)(70). G4DNA taken up by cells causes various biological responses including apoptosis in tumor cells (69, 71).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting STAT3 signaling by introducing dominant-negative constructs, decoy oligonucleotides, or antisense oligonucleotides to HNSCC cells significantly inhibits growth and induces apoptosis (26). Because persistent activation of STAT3 promotes tumor cell proliferation and survival, further contributing to tumor progression and migration, abrogation of STAT3 signaling is emerging as a potential cancer therapy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutively activated STAT3 activity has been routinely observed in multiple human cancers including lung, gastric, skin, head and neck, ovarian, breast, colon, and prostate (Bromberg et al, 1999;Bowman et al, 2000;Yu and Jove, 2004;Hsieh et al, 2005;Lin et al, 2005;Yin et al, 2006;Sansone et al, 2007;Abdulghani et al, 2008). In vitro and animal models have shown that inactivation of STAT3 inhibited carcinogenesis and the growth of established tumors, while enhancing expression of this gene promoted tumor incidence and growth (Yu and Jove, 2004;Jing et al, 2006;Siddiquee et al, 2007a,b;Weerasinghe et al, 2007;Bollrath et al, 2009). Moreover, activation of STAT3 has been associated with advanced stages of prostate cancer (Horinaga et al, 2005) and metastatic progression of several different cancer types, including lung cancer (Dauer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%